ROLE OF FOREIGN DIRECT INVESTMENT (FDI) IN INDIAN BANKING SYSTEM-AN OVERVIEW - Harshanya; Dr. N. Roopalatha; Dr. P. Sridhar (The journal of contemporary issues in business and government, 2022)
The Indian banking sector has established a critical platform for the country’s economic progress and wealth formation. The banking system is the pivot around which the economy of a country revolves. Any economy’s backbone is a functioning banking system. The importance of banks in the growth and development of any economy cannot be overstated. This does not need to be stated again. Since the liberalization and reforms of 1991, the Indian banking industry has changed dramatically, and Indian banks have expanded far outside their traditional regions of operation. One of the important initiatives in a broader reform agenda was to open up the Indian banking sector to international participation. India currently allows a total foreign participation in private banks of up to 1 billion